Peranan Merek Lokal dalam Pertumbuhan Ekonomi di Indonesia dalam Perspektif Teori Neo Klasik: Studi pada Perusahaan Sepatu Nah Project - Wijaya, Rossy Sapta; Wimbawani, Wiwik; Nata, Andrian Anwar L (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2024)
Economic growth is the process of changing the economic conditions of a country continuously towards the better. In Indonesia itself, MSMEs contribute significantly to increasing Gross Domestic Product, which of course MSMEs have an important role in Indonesia's economic growth. On the other hand, the role of local brands, especially fashion, in Indonesian MSMEs ranks first as MSME products that have experienced significant development. The research method in this study is qualitative descriptive, where all data sources are obtained based on literature and previous research that is studied using neoclassical theory. The results of the study revealed that (1) local brands have a large contribution to economic growth through job creation. Logically, the more new MSMEs are opened, the more employees they recruit, (2) local brands use digitalization in all lines of their operational activity processes, which means that local brands in MSMEs are able to contribute to increasing economic growth based on technological advances, and (3) since the Covid-19 pandemic, the government has provided soft loans to MSME business actors, and with this capital, it can increase the productivity of new and existing MSMEs.